2022
DOI: 10.3390/jof8101100
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Oleaginous Yeast from Mountain Forest Soil in Thailand

Abstract: As an interesting alternative microbial platform for the sustainable synthesis of oleochemical building blocks and biofuels, oleaginous yeasts are increasing in both quantity and diversity. In this study, oleaginous yeast species from northern Thailand were discovered to add to the topology. A total of 127 yeast strains were isolated from 22 forest soil samples collected from mountainous areas. They were identified by an analysis of the D1/D2 domain of the large subunit rRNA (LSU rRNA) gene sequences to be 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 83 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…mucilaginosa , Cystobasidium slooffiae , Naganishia diffluens , Pa. flavescens , Pa. terrestris , and Sa. podzolica (Sapsirisuk et al, 2022). In some forest types, the yeasts of other forest habitats were also studied.…”
Section: Yeast Diversity In Tropical Forests Of Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…mucilaginosa , Cystobasidium slooffiae , Naganishia diffluens , Pa. flavescens , Pa. terrestris , and Sa. podzolica (Sapsirisuk et al, 2022). In some forest types, the yeasts of other forest habitats were also studied.…”
Section: Yeast Diversity In Tropical Forests Of Asiamentioning
confidence: 99%
“…In tropical forest biomes, it is important to determine the composition of yeast species in a habitat, to distinguish prevalent from transient species, to identify the physiological traits that allow the colonization of each habitat, and to characterize the ecological interactions that contribute to ecosystem functioning. Yeast surveys have revealed that many species are specialists in some habitats, such as the surface and guts of insects and other animals, rotting plant materials, the phylloplane, flowers, soil, and water (Barros et al, 2023; Gomes et al, 2015; Lachance, Klemens, et al, 2001; Morais et al, 2017; Santos et al, 2018; Sapsirisuk et al, 2022; de Vega et al, 2017). Tropical forests provide an abundance of substrates for yeast colonization, and studies of these ecosystems are essential to understand the genetic diversity of yeasts, their biogeography, their interactions with other organisms, and their ecological role, as well as their biotechnological potential.…”
Section: Introductionmentioning
confidence: 99%
“…The soil contains a diverse range of microorganisms, with bacteria and fungi being the most abundant [4]. Studies have shown that in alpine meadows the bacterial community is mainly composed of Proteobacteria and Acidobacteria, and the most numerous fungal communities are Ascomycota and Basidiomycota, and not only with high plasticity and adaptability to the environment, but also, perform a vital function in crucial processes such as plant production, greenhouse gas emissions, and nutrient cycling, which are essential for the maintenance of numerous ecosystem functions [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Today, only 11% of the 1,600 known yeast species have been classified as oleaginous species (Abeln and Chuck 2021;Sapsirisuk et al 2022). Oleaginous yeast genera have commonly been isolated from different environments, such as fruit products, common surfaces, and soil (Vincent et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oleaginous yeast genera have commonly been isolated from different environments, such as fruit products, common surfaces, and soil (Vincent et al 2018). The soil is considered a reservoir for yeasts in underground environments (Sapsirisuk et al 2022). They belong to various genera within Candida, Cryptococcus, Kluyveromyces, Lipomyces, Rhodosporidium, Rhodotorula, Trichosporon, and Yarrowia (Dey and Maiti 2013;Jiru et al 2016;Gientka et al 2017;Patel et al 2017;Qin et al 2017;Ayadi et al 2018;Lopes et al 2018;Hoondee et al 2019).…”
Section: Introductionmentioning
confidence: 99%